Pemanfaatan Limbah Kulit Ikan Marlin (Makaira nigricans) sebagai Sumber Gelatin dengan Pretreatment Asam Kandis - Viona Oktafiani; Syamsi Aini (MASALIQ, 2026)
Marlin fish skin is a by-product of the fisheries industry that contains collagen and has the potential to be utilized as an alternative gelatin raw material, but its utilization through natural acid-based pretreatment and ultrasonically assisted extraction remains limited. This study aims to evaluate the utilization of marlin fish skin waste as a source of gelatin through kandis acid pretreatment and ultrasonically assisted extraction. This study used an experimental method with pretreatment stages using kandis acid, followed by extraction using an ultrasonic bath. The resulting gelatin was analyzed based on yield, physicochemical properties, and functional groups using Fourier Transform Infrared Spectroscopy (FTIR). The results of the study show that marlin fish skin gelatin produced a yield of 9.20%, moisture content of 9.91%, ash content of 0.49%, fat content of 1.99%, pH of 6.56, viscosity of 2.33 cP, melting point of 21°C, and gel point of 3°C. The moisture content, ash content, fat content, pH, and viscosity values met the quality requirements of SNI 06-3735-1995 and GMIA (2019). FTIR analysis identified Amide A bands at 3275 cm⁻¹, Amide I at 1632 cm⁻¹, Amide II at 1530 cm⁻¹, and Amide III at 1242 cm⁻¹, indicating similarity to standard gelatin. The conclusion of the study affirms that marlin fish skin waste can be utilized as a source of gelatin through kandis acid pretreatment and ultrasonically assisted extraction, with physicochemical characteristics that meet quality requirements. These findings have implications for developing the utilization of fisheries by-products as value-added alternative gelatin raw materials and have the potential to support the development of commercial gelatin products.